2003
DOI: 10.1901/jaba.2003.36-187
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Inappropriate Mealtime Behaviors

Abstract: The purpose of the current investigation was to apply the functional analysis described by Iwata, Dorsey, Slifer, Bauman, and Richman (1982/1994) to the inappropriate mealtime behaviors of 15 children who had been referred to an intensive program for the assessment and treatment of severe feeding disorders. During Study 1, we conducted descriptive assessments of children and parents during meals. The results of Study 1 showed that parents used the following consequences for inappropriate mealtime behaviors: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
218
4
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(254 citation statements)
references
References 28 publications
21
218
4
3
Order By: Relevance
“…Piazza, Fisher, et al (2003) described a method for conducting descriptive and experimental analyses of IMB. To complete the descriptive assessment, they observed caregiver-fed meals for six childparent dyads, scored both child responses (e.g., food acceptance, refusal) and parent responses (e.g., removal of demand, provision of attention and access to tangibles) and evaluated which parent responses most frequently followed child responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Piazza, Fisher, et al (2003) described a method for conducting descriptive and experimental analyses of IMB. To complete the descriptive assessment, they observed caregiver-fed meals for six childparent dyads, scored both child responses (e.g., food acceptance, refusal) and parent responses (e.g., removal of demand, provision of attention and access to tangibles) and evaluated which parent responses most frequently followed child responses.…”
mentioning
confidence: 99%
“…Although Piazza, Fisher et al (2003) conducted descriptive assessments to identify potential consequences following IMB, the parent responses were grouped into fairly broad categories and they did not specifically compare the likelihood of a parent response (following IMB) to the unconditional probability of the same response. That is, although it is helpful to know that a parent attends to a child following food refusal, this information does not tell us if attention following food refusal is a concern.…”
mentioning
confidence: 99%
“…Researchers have also shown that food refusal is consistent with an escape or avoidance function, such as a physical resistance to feeding, expulsion of food, or other incompatible behaviors such as aggression and attempts to leave the table (Piazza et al, 2003). The inappropriate behavior these children display tends to be higher when inappropriate behavior resulted in escape or breaks from bites of food, and for some when inappropriate behavior resulted in adult attention or tangible items.…”
Section: How Does Health Affect Problem Behavior?mentioning
confidence: 99%
“…Undiagnosed and/or untreated health problems may reduce a person's life expectancy and contribute to the development of secondary health complications (Cooper, Melville, & Morrison, 2004;Piazza et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation